Booming markets for Moroccan argan oil appear to benefit some rural households while threatening the endemic argan forest - Lybbert, Travis J.; Aboudrare, Abdellah; Chaloud, Deborah; Magnan, Nicholas; Nash, Maliha (Proceedings of the National Academy of Sciences, 2011)
Morocco's argan oil is now the most expensive edible oil in the world. High-value argan markets have sparked a bonanza of argan activity. Nongovernmental organizations, international and domestic development agencies, and argan oil cooperatives aggressively promote the win–win aim of simultaneously benefiting local people and the health of the argan forest. This paper tests some of these win–win claims. Analysis of a panel of detailed household data suggests that the boom has enabled some rural households to increase consumption, increase their goat herds (which bodes poorly for the argan forest), and send their girls to secondary school. The boom has predictably made households vigilant guardians of fruit on the tree, but it has not incited investments in longer term tree and forest health. We evaluate landscape-level impacts of these changes using commune-level data on educational enrollment and normalized difference vegetation index data over the period from 1981 to 2009. The results of the mesoanalysis of enrollment are consistent with the microanalysis: the argan boom seems to have improved educational outcomes, especially for girls. Our normalized difference vegetation index analysis, however, suggests that booming argan prices have not improved the forest and may have even induced degradation. We conclude by exploring the dynamic interactions between argan markets, local institutions, rural household welfare, and forest conservation and sustainability.